EXISTING PROBLEMS IN THE MANAGEMENT OF PUBLIC EXTERNAL DEBT AND WAYS TO ELIMINATE THEM - Chorieva Zebiniso Abdukarimovna (Journals Park Publishing, 2024)
The article covers factors affecting it in improving the management of public debt, controlling budget debt and budget spending, managing public debt. In order to make more effective use of foreign debt in the article, the analysis of its state and practice in the country, as well as the analysis of the practice of foreign countries, to identify the problems that arise in the effective management of State foreign debt
Keywords: public debt, jaxon Bank, budget, public external debt, public budget, financial market, global economy, investment activities, Enterprise Finance, Financial Planning, currency policy, foreign debt, domestic debt, Central bank.